Legal studies on mobile internet in an effort to prevent the negative impact of information and communication technology in Indonesia - Dudi Badruzaman (Journal of Law Science, 2023)
The development of information technology is not only capable of creating a global world but has also developed space for new life for society, namely the life of virtual society. However, it is undeniable that not all internet activities are always positively charged but the internet also has a negative side. Therefore, there must be countermeasures for the negative impacts of information technology that are more effective and preventive in nature. The aims of this research are: 1) To find out the negative impact of mobile internet usage in Indonesia. 2) To find out legal efforts to prevent the negative impact of information technology in Indonesia. 3) To find out the sanctions and regulations that can be used to ensnare perpetrators of mobile internet abuse in Indonesia. This study uses a normative juridical approach. The method used is a qualitative method. The data sources in this study consist of primary, secondary and tertiary. Data analysis was carried out by studying, interpreting the data that had been collected to draw a research conclusion and using a field approach, namely by conducting discussions on internet crime cases. So that a conclusion can be obtained as an answer to the problems discussed in this study.